A study of abuse including physical, substance, and sexual abuse among urban adolescent children - Sanjeeva, G N; Patil, Alkarani T; Kumar, Pragalatha (Indian Journal of Child Health, 2015)
Background: Adolescents are the future citizens of a country, and it is imperative to systematically address their needs. The prevalence of abuse including physical and sexual, by these adolescents as well as against them, have been increased. Objective: The study was undertaken to estimate the prevalence of abuse including physical, substance, and sexual abuse in adolescents of Bengaluru urban. Materials and Methods: This was a cross-sectional survey conducted among the adolescents aged 10-19 years in Bengaluru. A pretestedself-designed semi-structured questionnaire which included demographic profile and details of the substance abuse (physical and sexual abuse), juvenile delinquency was used. Data were analyzed using SPSS software. Results: A total of 303 adolescents were enrolled during the study period, out of which 167 adolescents were from school and 136 adolescents from the slum. Most children (54.1%) belonged to the age group of 14-16 years. Smoking (48.5%) was the most common form of abuse among the parents. The most commonsubstance abuse seen among children was smoking (30%). Majority were involved in violence with other adolescents (71%). Sexual abuse was seen more in slum children as compared to school children. Substance abuse among children was mostly influenced by friends in 70 (40.7%) cases. Conclusion: Substance abuse was common in male slum adolescents for which peer pressure and curiosity were the main influences. More than one-quarter of slum adolescents reported physical abuse while sexual abuse was more commonly reported in female slum adolescents.